Pay as You Drink for Sustainability of Community Water Projects - Anne Wairimu Ndiritu; Solomon Muriungi Mburung’a; Caroline Njoki Ndiritu (European Scientific Journal, ESJ, 2018)
The main objective of this study was to investigate how community water projects are influenced by water user fee payment by the stakeholders. This studywas carried out in Kieni Constituency, Nyeri County in Kenya. The research was based on the models of sustainability and theories of capital structure. The study was carried out in all the 73 water projects in Kieni Constituency. The units of analysis were all the chairmen of these projects together with 381 beneficiaries of the water projects. Two district water officers and 9 local bank managers were also included in the study. Structured questionnaires, interview and observation schedules were used as research instruments. Pearson’s Product Moment correlation was used in ascertaining the relationships between the study variables and F statistic was used in testing the hypothesis that: there is no significant relationship between the amount of water user fees and sustainability of community water projects. The analysis showed that there was a correlation coefficient r=0.356 depicting a moderate positive correlation which was significant at 0.10 significant level. This indicated a significant moderate positive relationship between water user fee and sustainability of community water projects. It was therefore concluded that an increase in water user fee moderately improves sustainability of community water projects. From the study findings, it was recommended that there is need to establish a sufficient level of water user fee and also a proper management of the collected water user payments